The genetic link between the Azores Archipelago and the Southern Azores Seamount Chain (SASC): The elemental, isotopic and chronological evidences - Pinto Ribeiro, Luísa (2017)
New geochemical, isotopic (Sr-Nd-Hf-Pb) and K-Ar data, are presented here on samples from the Southern Azores Seamount Chain (SASC) located south of the Azores Plateau. The SASC also includes the Great Meteor, Small Meteor and Closs seamounts, morphologically connected by a saddle at −4100 m deep. We conclude that the SASC are characterized by a narrow isotopic variability that falls within the Azores isotopic field. Although each seamount has its own isotopic signature, their mantle source must comprise four local mantle end-members, three of which are common to the Azores, e.g. Plato isotopic signature results fromthe mixing between HIMU and N-MORBwhile GreatMeteor signature results fromthis mix with the Azores Common Component (AzCC). A fourth end-member with high 208Pb/204Pb and decoupled Th/U ratios (Δ8/4 up to 59.2) is identified on Great Meteor northern flank. New K-Ar ages on Plato (33.4 ± 0.5 Ma) and Small Hyeres (31.6 ± 0.4 Ma) show nearly coeval volcanism,which is contemporaneouswith the E-MORBs erupted at theMAR, drilled on oceanic crust with 30-34 Ma (DSDP82). This study endorses the genetic link between the Azores Archipelago and the SASC to the long-termactivity of the Azores plumeand the large-scale ridge-hotspot interaction, contributing to better constrain the temporal-spatial evolution of this region of the North Atlantic.